Studi Keragaman Jenis dan Pola Sebaran Tumbuhan Pakan Burung Madu di Taman Wisata Alam Baumata, Kabupaten Kupang, Provinsi Nusa Tenggara Timur - M. Martyn De Pores N. Olin; Maria M. E. Purnama; Fadlan Pramatana; Roni Haposan Sipayung (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2026)
This study aimed to analyze the diversity and spatial distribution of nectar-producing plants for sunbirds (honeyeaters) in the Baumata Natural Recreation Park (TWA), East Nusa Tenggara. An exploratory survey was conducted using a systematic sampling technique. Sampling plots were established at 100-meter intervals, consisting of nested sub-plots categorized by growth stages. The data were analyzed using the Importance Value Index, the Shannon-Wiener Diversity Index (H'), and the Morisita Dispersion Index. The results identified eight species of forage plants. Three species were confirmed as actual forage plants due to direct consumption observations : Senna siamea, Gliricidia sepium, and Gmelina arborea. Meanwhile, five other species, including Alstonia scholaris, Tectona grandis, Ficus benjamina, Bauhinia purpurea, and Hibiscus rosa-sinensis, were categorized as potential forage plants. According to the Morisita Index, all identified forage plants exhibited a clumped distribution pattern. These findings suggest that enrichment planting programs focusing on both actual and potential forage species are essential to ensure food availability and support the long-term conservation of sunbirds in TWA Baumata.